2011
DOI: 10.1128/jb.01257-10
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Regulator and ABC Transporters Link Stress Tolerance, (p)ppGpp, and Genetic Competence in Streptococcus mutans

Abstract: Streptococcus mutans, a primary agent of dental caries, has three (p)ppGpp synthases: RelA, which is required for a mupirocin-induced stringent response; RelP, which produces (p)ppGpp during exponential growth and is regulated by the RelRS two-component system; and RelQ. Transcription of relPRS and a gene cluster (SMu0835 to SMu0837) located immediately upstream was activated in cells grown with aeration and during a stringent response, respectively. Bioinformatic analysis predicted that SMu0836 and SMu0837 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 47 publications
2
108
1
Order By: Relevance
“…Reporter strains containing fusions of the promoter regions of the fructosyltransferase gene (ftf) and the nonlantibiotic mutacin D gene (nlmD) were constructed by amplifying the promoter region and the ribosome-binding site (RBS) of each gene from S. mutans UA159 and cloning them in front of the staphylococcal chloramphenicol acetyltransferase gene (cat) lacking its intrinsic promoter and RBS, resulting in strains with Pftf-cat and PnlmD-cat reporter fusions, respectively. The PnlmD-cat fusion was introduced as a single copy into the mtlA-phn region of the chromosome of S. mutans UA159 using the integration vector pJL105 (50). For the Pftf-cat reporter fusion, plasmid pBGK was used as the integration vector to introduce the fusion as a single copy in the gtfA gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporter strains containing fusions of the promoter regions of the fructosyltransferase gene (ftf) and the nonlantibiotic mutacin D gene (nlmD) were constructed by amplifying the promoter region and the ribosome-binding site (RBS) of each gene from S. mutans UA159 and cloning them in front of the staphylococcal chloramphenicol acetyltransferase gene (cat) lacking its intrinsic promoter and RBS, resulting in strains with Pftf-cat and PnlmD-cat reporter fusions, respectively. The PnlmD-cat fusion was introduced as a single copy into the mtlA-phn region of the chromosome of S. mutans UA159 using the integration vector pJL105 (50). For the Pftf-cat reporter fusion, plasmid pBGK was used as the integration vector to introduce the fusion as a single copy in the gtfA gene.…”
Section: Methodsmentioning
confidence: 99%
“…Colonies were counted after 48 h of incubation at 37°C in a 5% CO 2 aerobic atmosphere. Transformation efficiency was expressed as the number of transformants divided by the total number of viable cells; this number was then multiplied by 100 to obtain percentage of transformants (50).…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that RelRS is involved in the regulation of (p)ppGpp metabolism (127). The environmental signals to which RelRS responds have not been determined, although it has been suggested that RelRS may sense oxidative stressors or by-products of oxidative metabolism (131). Expression of relPRS is regulated by the MarR family transcriptional regulator RcrR, which is involved in stress tolerance and competence, although the signals to which RcrR responds remain unidentified (131,132).…”
Section: The Stringent Response: the Ribosome As A Sensormentioning
confidence: 99%
“…For example, SASs might respond to different internal or external cues than the Rel enzyme. In support, there is evidence of transcriptional induction of the Bacillus subtilis, Staphylococcus aureus, and Streptococcus mutans SASs under alkaline, cell wall, or oxygen stresses, respectively (22,24,30). Alternatively, they might differ from long RSH enzymes because their constitutive synthetase activity ensures persistent basal (p)ppGpp production (21,28).…”
mentioning
confidence: 99%